Perception of and attitude toward ethical issues among Korean occupational physicians - Choi, Junghye (Ann Occup Environ Med, 2017)
BACKGROUND: Occupational physicians (OPs) have complex relationships with employees, employers, and the general public. OPs may have simultaneous obligations towards third parties, which can lead to variable conflicts of interests. Among the various studies of ethical issues related to OPs, few have focused on the Korean OPs. The aim of the present survey was to investigate the ethical contexts, the practical resolutions, and the ethical principles for the Korean OPs. METHODS: An email with a self-administered questionnaire was sent to members of the Korean Society of Occupational and Environmental Medicine, comprising 150 specialists and 130 residents. The questionnaire was also distributed to 52 specialists and 46 residents who attended the annual meeting of the Korean Association of Occupational and Environmental Clinics in October 2015, and to 240 specialists by uploading the questionnaire to the online community ‘oem-doctors’ in February 2016. The responses to each question (perception of general ethical conflicts, recognition of various ethical codes for OPs, core professional values in ethics of occupational medicine, and a mock case study) were compared between specialists and residents by the chi-squared test and Fisher’s exact test. RESULTS: Responses were received from 80 specialists and 71 residents. Most participants had experienced ethical conflicts at work and felt the need for systematic education and training. OPs suffered the most ethical conflicts in decisions regarding occupational health examination and evaluation for work relatedness. Over 60% of total participants were unaware of the ethical codes of other countries. Participants thought ‘consideration of worker’s health and safety’ (26.0%) and ‘neutrality’ (24.7%) as the prominent ethical values in professionality ofoccupational medicine. In mock cases, participants chose beneficence and justice for fitness for work and confidential information acquired while on duty, and beneficence and respect for autonomy in pre-placement examinations. CONCLUSIONS: This study evaluated the current perception of and attitude toward ethical issues among the Korean OPs. These findings will facilitate the development of a code of ethics and the ethical decision-making program forthe Korean OPs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40557-017-0182-z) contains supplementary material, which is available to authorized users.